2008
DOI: 10.1530/rep-07-0300
|View full text |Cite
|
Sign up to set email alerts
|

Presence, processing, and localization of mouse ADAM15 during sperm maturation and the role of its disintegrin domain during sperm–egg binding

Abstract: Successful fertilization requires gametes to complete several stages, beginning with maturation and transport along the male and female reproductive tracts and ending with the interaction between the sperm and the egg. This last step involves sperm-egg adhesion and membrane fusion. ADAMs (disintegrin and metalloprotease domain proteins) are a family of membrane-anchored glycoproteins that are thought to play diverse roles in cell-cell adhesion through their interaction with integrins. This study analyzes the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 43 publications
1
34
0
1
Order By: Relevance
“…In the same way as the principal piece, the cytoskeleton associated with PM in the acrosomal region is mainly composed of spectrin/F-actin, but with the difference that it is remodeled during capacitation. During capacitation and AR, proteins associated with PM as well as with membrane lipids compartmentalize in the acrosome region; they are redistributed inside the acrosome or distribute towards the equatorial segment and postacrosomal region as well (Rochwerger & Cuasnicu 1992, Da Ros et al 2004, Selvaraj et al 2007, Tsai et al 2007, Pasten-Hidalgo et al 2008. These molecules in some way are maintained as compartmentalized in the acrosome before capacitation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the same way as the principal piece, the cytoskeleton associated with PM in the acrosomal region is mainly composed of spectrin/F-actin, but with the difference that it is remodeled during capacitation. During capacitation and AR, proteins associated with PM as well as with membrane lipids compartmentalize in the acrosome region; they are redistributed inside the acrosome or distribute towards the equatorial segment and postacrosomal region as well (Rochwerger & Cuasnicu 1992, Da Ros et al 2004, Selvaraj et al 2007, Tsai et al 2007, Pasten-Hidalgo et al 2008. These molecules in some way are maintained as compartmentalized in the acrosome before capacitation.…”
Section: Discussionmentioning
confidence: 99%
“…Capacitation in the presence and absence of ALLN or calpeptin Capacitation was performed as described elsewhere (CabelloAgueros et al 2003, Pasten-Hidalgo et al 2008; briefly, ductus deferens guinea pig sperm were obtained and washed in 154 mM NaCl solution. Sperm cells (3.5!10 7 cell/ml) were capacitated by incubation at 37 8C in MCM-PL without glucose.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The major variant at this locus is conserved across all known SPACA3 orthologs, indicating its importance to the functioning of SPRASA. This variant is located within the seed region for hs-miR873, a miRNA Pasten-Hidalgo et al, 2008) that can specify posttranscriptional repression by transcript destabilisation/translational repression (Friedman et al, 2009). The identifi cation of hs-miR873 and the conservation of this region suggest that this locus may be important in the regulation of SPACA3 by affecting the stability and/or translation of the mRNA, thereby affecting levels of the SPRASA protein.…”
Section: Discussionmentioning
confidence: 99%
“…The heterodimer ADAM1/ADAM2, also known as fertilin a/b, which plays an important role in sperm-egg interaction during fertilization, is the best-studied of the ADAM family (Myles et al 1994, Evans et al 1995, Cho et al 1998, Chen et al 1999. Another well-studied example is ADAM15, which is expressed on the surface of a wide range of somatic cells and in mouse spermatozoa, has a role as an adhesion protein (Herren et al 1997, Poghosyan et al 2002, Pasten-Hidalgo et al 2008. We have recently reported that ADAM15 is expressed in mouse spermatozoa.…”
Section: Introductionmentioning
confidence: 99%